Analysis of the Distribution Pattern Environmental Risk Factors with the Incidence Dengue Hemorrhagic Fever in South Binjai District, Binjai City - Mustar Rusli; Samuel Marganda Halomoan Manalu; Deli Syaputri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Environmental conditions have a big influence on the incidence of dengue hemorrhagic fever, because a bad environment can increase the breeding and reproduction of the Aedes aegypti mosquito. Research Objectives: To determine environmental risk factors and distribution patterns of dengue hemorrhagic fever in South Binjai District, Binjai City. The type of research used was analytical observational research with a cross sectional design and an ecological approach. The population in this study was 54.422 people and a sample of 100 people. Analysis of research data with bivariate using Chi square test. And mapping analysis of the distribution of cases of Dengue Hemorrhagic Fever using the Geographic Information System application to describe the distribution pattern of Dengue Hemorrhagic Fever in Binjai City. The results of the study showed that there was a relationship between the presence of larvae and cases of dengue hemorrhagic fever (p-value=0.000), there was a significant relationship between the presence of larvae and cases of dengue hemorrhagic fever (p-value=0.000), there was a significant relationship between the habit of hanging clothes with cases of dengue hemorrhagic fever (p-value=0.000), there is a significant relationship between the frequency of draining the bathtub and cases of dengue hemorrhagic fever (p-value=0.004), there is no significant relationship between the frequency of support from health workers and cases of dengue hemorrhagic fever (p-value = 0.359), and there is no significant relationship between the frequency of experience of receiving health education and cases of dengue hemorrhagic fever (p-value = 0.359). The distribution of dengue fever cases is not spread throughout the sub-district, but only in several adjacent areas. Based on research results, the highest number of cases occurred in mixed plantation areas. It is recommended that health workers compile a more specific distribution pattern map regarding the factors causing Dengue Hemorrhagic Fever.Keywords: Dengue hemorrhagic fever, Distribution pattern, Environmental, Risk factors